Choosing Doctors Wisely: Can Assisted Choice Enhance Patients' Selection of Clinicians?. (October 2019) - Martino, Steven C.; Grob, Rachel; Davis, Sarah; Parker, Andrew M.; Finucane, Melissa L.; Cerully, Jennifer L.; Rybowski, Lise; Shaller, Dale; Schlesinger, Mark
We conducted a simulated clinician-choice experiment, comparing choices and decision-making processes of participants ( N = 688) randomized among four experimental arms: a conventional website reporting only quantitative performance information, a website reporting both qualitative (patient comments) and quantitative information, the second website augmented by a decision aid (labeling of patient comments), and the decision-aided website further augmented by the presence of a trained navigator. Introducing patient comments enhanced engagement with the quality information but led to a decline in decision quality, particularly the consistency of choices with consumers' stated preferences. Labeling comments helped erase the decline in decision quality, although the highest percentage of preference-congruent choices was seen in the navigator arm. Engagement with the quality information and satisfaction with choices available were likewise highest in the navigator arm. Findings held for high- and low-skilled decision makers. Thus, navigator assistance may be a promising strategy for equitably promoting higher quality choices in information-rich contexts.